PENGARUH PUPUK HIJAU Tithonia diversifolia TERHADAP PERTUMBUHAN DAN HASIL TANAMAN JAGUNG (Zea mays L.) - Priyo Hutomo,Mahfudz, Syamsuddin Laude, Ifan (AGROTEKBIS, 2015)
This research aim to stay the effect green manure dose of Tithonia diversifolia on growth and result of maize crop (Zea mays L.) in farmer farm in Sidera of Sub district Sigi Biromaru of Regency Sigi, Mei-Juli 2013. Field experiment the Random Device Blok Disaign (RAK) consisted of 4 treatment, that is B1 = Without green manure, B2 = Green Manure of Tithonia diversifolia 5 ton of per ha, B3 = Green Manure of Tithonia Diversifolia 10 ton of per ha, B4 = Green Manure of Tithonia diversifolia 15 ton of per ha. Every treatment repeated three of times, consisted of 12 unit. Result indicate that the green manure Tithonia diversifolia can improve the growth and result of maize crop (Zea mays L.) With the green manure of Tithonia Dose 10 (ton) per ha can improve result of maize crop equal to 9.2 ton / ha.